Development of collaborative spirit indices: The case of South Korea's maritime industry - Chang-Soo Kim; Saeyeon Roh; Young-Joon Seo (Asian Journal of Shipping and Logistics (AJSL), 2022)
This study aims to evaluate the extent of collaboration between shippers and shipping companies in South Korea. Bespoke cooperative and collaborative spirit indices (CCSIs) reflect the conceptual differentiation between cooperation and collaboration, as well as a more comprehensive conceptualisation. Shipping companies registered in South Korea returned 167 usable responses. CCSIs were developed through exploratory factor analysis weighting methods, and differences among CCSIs by vessel type and contract period were examined using multivariate analysis of variance. CCSIs indicate that powerful supply chain members resist two-way communication, mutuality, distributive fairness, and long-term relationships. This is one of the first studies to operationalise the key concepts of cooperation and collaboration in terms of the maritime industry, providing the basis for future research in other supply chains despite a single informant attribute. Based on the CCSI scores, managerial and political initiatives are discussed to reduce barriers to interaction and ameliorate the CCSI level between supply chain members. The research provides insights into the extent of cooperation and collaboration by initially establishing CCSIs in the maritime industry, which will support strategic approaches to supply chain members.
Keywords: 650; Collaboration; Cooperation; Empirical study; Marine transport; South Korea